2016
DOI: 10.1073/pnas.1610515113
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of male pheromone response in the European corn borer identifies candidate genes regulating neurogenesis

Abstract: The sexual pheromone communication system of moths is a model system for studies of the evolution of reproductive isolation. Females emit a blend of volatile components that males detect at a distance. Species differences in female pheromone composition and male response directly reinforce reproductive isolation in nature, because even slight variations in the species-specific pheromone blend are usually rejected by the male. The mechanisms by which a new pheromone signal-response system could evolve are enigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 81 publications
(72 reference statements)
1
34
0
Order By: Relevance
“…Although recombination suppression is directly observed in our single between‐strain pedigree, Koutroumpa et al . () found a major QTL for male pheromone response segregating among collinear sex chromosomes. Furthermore, at Landisville where bivoltine populations occur and sampled males came from E or Z pheromone‐specific traps (Linn et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although recombination suppression is directly observed in our single between‐strain pedigree, Koutroumpa et al . () found a major QTL for male pheromone response segregating among collinear sex chromosomes. Furthermore, at Landisville where bivoltine populations occur and sampled males came from E or Z pheromone‐specific traps (Linn et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Koutroumpa et al . ). Blastn searches of GBS sequences against amplicons identified shared markers.…”
Section: Methodsmentioning
confidence: 97%
“…Such an imbalance in mating success and selection for advantageous introgressed alleles within hybrid zones may impact the observed displacement of O. nubilalis from the region, but additional investigation is warranted. The genetics of male Ostrinia pheromone response is yet to be fully resolved, but is known to involve genes on the Z chromosome that may influence neural development (Dopman, Bogdanowicz, & Harrison, ; Koutroumpa et al., ). The role of this potentially “hardwired” male response in relation to the functionally divergent Z chromosome‐linked OR4 (Leary et al., ) and courtship behaviour remains unknown, and it is intriguing to hypothesize about the impact of hybridization of F 1 and backcross males in regard to mate preferences as determined by species origin and epistatic interaction of genes on the Z chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated that a small proportion of males of both O. nubilalis and O. furnacalis responded to interspecific female pheromone blends at long distances within nonchoice wind tunnel experiments (Linn, Musto, & Roelofs, ; Linn, O'Connor, & Roelofs, ; Martin, Moore, Musto, & Linn, ). The basis of this interspecies sex pheromone response of these “rare” males was found to reside within the lack of antagonistic neuron signalling (Domingue, Musto, Linn, Roelofs, & Baker, ), but the exact structural or functional changes that give rise to these neurological responses downstream of OR4 are yet to be resolved (Groot, Dekker, & Heckel, ; Koutroumpa, Groot, Dekker, & Heckel, ). Regardless, the asymmetric tracking hypothesis proposes that males respond to a greater diversity of pheromones compared the corresponding range of pheromones produced by cognate females within the same species (Phelan, ) and in doing so provide a reproductive advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of hybridization and positive assortative mating based on this autosomal marker vary among natural populations (Coates, Johnson, et al, 2013). Resp is located within a region of the Z-chromosome that encodes a suite of genes putatively involved in neuronal development and function (Koutroumpa, Groot, Dekker, & Heckel, 2016). In addition to Resp, a major QTL for voltinism differences between strains is located on the Z-chromosome (Dopman et al, 2004).…”
mentioning
confidence: 99%